2001
DOI: 10.1055/s-2001-16573
|View full text |Cite
|
Sign up to set email alerts
|

Wasserstrahldissektion bei Leberresektion: Ultraschallaspirator versus Jet-Cutter - Eine prospektiv randomisierte Studie -

Abstract: The jet-cutter-technique is a fast and safe surgical procedure for liver resections and offers an attractive therapeutic alternative for various indications in liver surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 12 publications
0
17
0
3
Order By: Relevance
“…Furthermore, more than half of the centers selected ligation with stitch to seal the thin portal pedicles. Those results might have arisen from the evidence that several randomized trials showed no superiority of other new techniques over classical clamp-crushing [9,10,11,12,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, more than half of the centers selected ligation with stitch to seal the thin portal pedicles. Those results might have arisen from the evidence that several randomized trials showed no superiority of other new techniques over classical clamp-crushing [9,10,11,12,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…The clamp-crushing technique and ultrasonic dissectors (CUSA), which were introduced in the 1970s [8] and in the 1990s [9,10], respectively, were the two major methods favored in many centers. Furthermore, more than half of the centers selected ligation with stitch to seal the thin portal pedicles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Наиболее популярной областью применения во-доструйных диссекторов в настоящий момент оста-ется хирургическая гепатология [11][12][13]. Мировая литература содержит множественные сообщения об использовании этой методики в нейрохирургии, хирургии печени, предстательной железы [8,14].…”
Section: Discussionunclassified